The Impact Of Fdi On Export In Syria - ديوب محمد; إسماعيل رولا; حسن حسين (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Foreign Direct Investment (FDI) is considered as an important means of promoting export of the host countries. By training the local work force and upgrading the technical and managerial skills, it helps in raising the efficiency and productivity of the factors and hence competitive strength in the international market. In addition to this, by facilitating access to large international market, FDI makes a significant positive contribution to the host country’s exports. However this is true if FDI comes for efficiency reason and not for domestic market. The present study examines the nature of relationship between export and FDI in Syria over the period 1990-2010. Using error correction model (ECM). the paper does not find a long run equilibrium relationship between FDI and export. The result of error correction model (ECM) shows that FDI inflow does not cause export in Syria. This is due to the decrease in the volume of foreign investment flowing into Syria, which requires working to improve the investment climate in Syria to attract more foreign direct investment.